PENDEKATAN RESTORATIVE JUSTICE SEBAGAI UPAYA PENYELESAIAN SCHOOL BULLYING - Widyawati, Anis (Faculty of Law, Universitas Sebelas Maret, 2014)
This research uses Socio Juridical approach by reviewing the pandects prevailing in the society, analyzing the implementation of Restorative Justice in settling and minimizing the cases of School Bullying, acquiring data related to the factors of school bullying, the characteristics of the bullies and the bullying facts, and digging up the efforts to overcome bullying , either for the victims, the witnesses, the school or the parents. This research uses in depth interview, observation and documentation. In depth interview is conducted on a number of respondents, namely the students of SMPN 3 Boja and the teachers on Guidance and Counseling. The result of the research shows that in the teaching and learning process and the extracurricular activities in SMPN 3 Boja, the forms of bullying including direct physical contact such as beating and pushing, direct verbal contact such as the acts of disgracing, name-calling, and mocking, direct non-verbal behaviors by sticking the tongue out, mocking, or threatening which are usually followed by physical or verbal bullying, and indirect nonverbal behaviors such as expelling someone from the group, manipulating friendship, and sending anonymous letter. According to the result of the research, the writer recommends the restorative justice approach as the solution in settling the school bullying in order to make the students be responsible for their actions. This approach should be applied by involving the victims and the relevant parties especially the family and the society to take role in mending the suspected children’s morality so that they will not feel as if they are prisoners who should be expelled from their environment and will have the motivation to improve themselves and not to repeat their mistakes. Lastly, the law upholder should adjust the Law No. 11/2012 on Juvenile Criminal Justice System in settling children as the criminal offenders.